A comprehensive model for production data analysis in unconventional reservoirs of hydrocarbons. (24th June 2020) - Chen, Zhiming; Chu, Hongyang; Chen, Haoshu; Zhang, Jiali
Abstract: Because of the large amount of energy-rich organic compound, shale gas reservoirs can be good sources of hydrogen energy. To ensure high yield of hydrogen energy, the production data analysis in those shale gas reservoirs is of great significance. However, due to geological and engineering factors, there exist complex mechanisms including stress-sensitivity effect of permeability, gas desorption, complex gas flows, multiple finite-conductivity fractures, and wellbore hydraulics. Unfortunately, little work has been done to focus on these complex mechanisms simultaneously. To comprehensively address this issue, this paper presents a comprehensive model by using a semi-analytical method, and those complex mechanisms are all considered by introducing adsorption index, Knudson diffusion coefficient, reservoir-wellbore constant, and Reynolds number. Both model verification and field application are performed. This study further narrows the gap between theory and practice of production data analysis in shale gas reservoirs, which helps to parameter evaluation, performance forecast, and productivity enhancement in the unconventional reservoirs of hydrocarbons. Highlights: Shale gas (SG) reservoirs can be good sources of hydrogen energy. Little work has been done on complex mechanisms simultaneously for SG production. A comprehensive model is proposed for PDA in SG reservoirs with complex mechanisms. Adsorption, Knudson diffusion, reservoir-wellbore constant, and Reynolds number. Providing guidelines for parameter evaluation and production forecast.